Laboratory investigations of the physical parameters influencing the in situ leaching of tungsten. (January 2021) - Osvald, Máté; Kilpatrick, Andrew; Rochelle, Christopher A.; Szanyi, János; Raucsik, Béla; Medgyes, Tamás; Kóbor, Balázs
Abstract: Tungsten leaching potential from geothermal reservoirs was investigated using a flow-through reactor with the characteristic physical properties of a geothermal reservoir. Tungsten minerals were tested at 200 °C, 250 °C and 300 °C, and 0.5 and 1.0 mL/min flow rates to determine the most favourable conditions for the mobilisation of tungsten. In situ leaching yielded tungsten concentrations of 1–182 mg/L in the leachates, with pure scheelite being the most effective in mobilising tungsten. The highest concentrations, which were obtained at 300 °C, were generally observed in the first 30–60 min because of the rapid fluid–rock interactions in the geothermal reservoir.